2019
DOI: 10.3389/fnbeh.2019.00105
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin Differentially Affects Handgrip Force of Expectant Fathers in Reaction to Own and Unknown Infant Faces

Abstract: The underlying mechanisms of paternal responses to infant signals are poorly understood. Vasopressin has previously been proposed to affect these responses. Using a double-blind, placebo-controlled, within-subject design ( N = 25 expectant fathers), we examined the effect of vasopressin administration on the use of excessive handgrip force during exposure to infant crying versus matched control sounds, while participants saw morphed images representing their own infant versus an unknown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 92 publications
0
23
0
Order By: Relevance
“…Similar preparatory mechanisms, including enhanced sensitivity to vasopressin, may be found in humans. Administering vasopressin to expectant fathers promoted attention to virtual baby‐related avatars (Cohen‐Bendahan, Beijers, Van Doornen, & de Weerth, ), and affected neural and behavioral responses to sounds of infants crying (Alyousefi‐Van Dijk et al, ; Thijssen et al, ), pointing to a role for vasopressin in responding to infant distress. Moreover, vasopressin levels may be related to fathers’ stimulatory interaction with their infants (Abraham & Feldman, ).…”
Section: A Biobehavioral Model Of Emergent Fatherhoodmentioning
confidence: 99%
“…Similar preparatory mechanisms, including enhanced sensitivity to vasopressin, may be found in humans. Administering vasopressin to expectant fathers promoted attention to virtual baby‐related avatars (Cohen‐Bendahan, Beijers, Van Doornen, & de Weerth, ), and affected neural and behavioral responses to sounds of infants crying (Alyousefi‐Van Dijk et al, ; Thijssen et al, ), pointing to a role for vasopressin in responding to infant distress. Moreover, vasopressin levels may be related to fathers’ stimulatory interaction with their infants (Abraham & Feldman, ).…”
Section: A Biobehavioral Model Of Emergent Fatherhoodmentioning
confidence: 99%
“…However, the intranasal administration of AVP has been shown to result in increased AVP concentrations in both cerebrospinal fluid and blood plasma of healthy adult men and women within 10 min, with effects still present after 80 min (Born et al, 2002). Furthermore, studies have shown that neurobiological systems involved in the processing of cry sounds (Thijssen et al, 2018), processing of infant-related visual stimuli (Cohen-Bendahan et al, 2015) and the activation of protective parenting (Alyousefi-van Dijk et al, 2019) are affected by the AVP nasal administration in prospective fathers. However, it remains unknown what specific neurobiological effects are evoked by AVP administration.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, no effect of AVP administration was observed in the neural response to infant stimuli in fathers of toddlers (Li, Chen, Mascaro, Haroon, & Rilling, 2017). It may thus be the case that AVP is particularly relevant during the transition to parenthood (Alyousefi-van Dijk et al, 2019).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Research has further shown that oxytocin and vasopressin affect neural and behavior responses to infant signals [4, 9, 10, 1214]. For example, a small functional magnetic resonance imaging (fMRI) study including fathers of 4- to 6-month-old infants reported a negative association between fathers’ endogenous vasopressin levels and activations in the inferior gyrus and insula when watching their own infant play, suggesting that lower vasopressin levels enhances social-cognitive and empathic responses, although replication of these findings in larger samples is needed [4].…”
Section: Introductionmentioning
confidence: 99%